2013
DOI: 10.1186/1471-2164-14-107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the global transcriptome for Pyropia haitanensis(Bangiales, Rhodophyta) and development of cSSR markers

Abstract: BackgroundPyropia haitanensis is an economically important mariculture crop in China and is also valuable in life science research. However, the lack of genetic information of this organism hinders the understanding of the molecular mechanisms of specific traits. Thus, high-throughput sequencing is needed to generate a number of transcriptome sequences to be used for gene discovery and molecular marker development.ResultsIn this study, high-throughput sequencing was used to analyze the global transcriptome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 56 publications
0
40
0
1
Order By: Relevance
“…In their study on the genome of C. crispus, Collén et al surprisingly found that there were only two genes encoding LOX but no candidates for AOS, HPL, and DES. The present study also searched the P. haitanensis transcriptomic information published by Xie et al [16] and the genomic data of P. yezoensis but did not find candidate genes for these enzymes. To date, no evidence has indicated that CYP74 family existed at the evolutionary stage when Rhodophyta emerged.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In their study on the genome of C. crispus, Collén et al surprisingly found that there were only two genes encoding LOX but no candidates for AOS, HPL, and DES. The present study also searched the P. haitanensis transcriptomic information published by Xie et al [16] and the genomic data of P. yezoensis but did not find candidate genes for these enzymes. To date, no evidence has indicated that CYP74 family existed at the evolutionary stage when Rhodophyta emerged.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, there is the question of whether these pathways evolved independently in the different kingdoms. In this study, a LOX gene from P. haitanensis (Bangiales, Rhodophytes), a typical warm, temperate zone species [16], was identified and its versatile functions and enzyme products described. The results raised interesting questions concerning this enzyme's evolutionary heritage and its relationship to the known diversity of oxylipin structures and functions.…”
Section: Introductionmentioning
confidence: 99%
“…Draft genome of Pyropia yezoensis has been released (Niu et al 2011;Nakamura et al 2013), and transcriptome of Pyropia and Porphyra has been compared for life stages and under stress (Chan et al 2012;Choi et al 2013;Xie et al 2013;Im et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about transcription level changes in response to dehydration. Efforts to sequence the genomes and transcriptomes of species such as Chondrus crispus, Gracilariopsis lemaneiformis, Pyropia yezoensis, Pyropia haitanensis, and Gracilaria changii are beginning to change this situation (Collén et al 2006b;2006a;Teo et al 2009;Choi et al 2012;Xie et al 2013;Zhou et al 2013;Kowalczyk et al 2014;Im et al 2015).…”
Section: Introductionmentioning
confidence: 99%